Hubungan Kepatuhan Ibu Bersalin Terhadap Bimbingan Meneran Dengan Rupture Perineum di RSUD Batara Siang - Hajratul Azward (Universitas Muhamadiyah Manado, 2021)
The causes of maternal death were bleeding (28%), infection (11%), eclampsia (24%), and obstructed or prolonged labor (5%). One of the causes of bleeding as a cause of AKI is perineal rupture. Perineal rupture is influenced by several factors, including: Maternal factors include maternal age, parity, pregnancy spacing, inappropriate delivery methods. Compliance with menstrual guidance is very necessary for the success of the birthing process to prevent perineal rupture. The aim of this study was to determine the relationship between maternal compliance with counseling and perineal rupture at Batara Siang Regional Hospital. The method used was analytical observational with a cross sectional approach, the sampling technique was purposive sampling with a total sample of 32 mothers giving birth. Results: There is a significant relationship between compliance with gentle guidance and the incidence of perineal rupture in mothers giving birth, seen from the results of non-parametric statistical analysis using the Spearman rank test and using SPSS 16 to obtain a significance or sign value. (2-failed) of 0.001.